Customer Decision to Distribute ZIS through BSI Mobile: The Influence of Trust and Easiness - Ilham, Muhamad; Haris, Helmi (Universitas Muhammadiyah Surakarta, 2024)
Purpose: This study aims to determine whether trust and ease are factors that influence Customer decisions to channel ZIS through BSI mobile. Methodology: This study's primary data source is BSI customers domiciled in Solo Raya who have had BSI mobile as the population. The data was tested using the Validity Test, Reliability Test, and Classical Assumption Test. Then, it was analyzed using Multiple Linear Regression, T-test, and F-test. Results: The results of the study showed that trust had a significant positive effect on Customer’s decisions to channel ZIS through BSI mobile. Easiness had a significant positive effect on Customer’s decisions to channel ZIS through BSI mobile. Simultaneously, trust and ease influence customer decisions to channel ZIS through BSI mobile. Applications/Originality/Value: This study can be used as a reference for mobile banking to provide easy and reliable services to customers so that economic flows, including ZIS, are better absorbed. Then, specifically, the BSI mobile application will be able to maintain public trust and provide a simpler application menu (easy to use).